Cutaneous metastases from rectal adenocarcinoma: A case report - Samia Rahman; Parbeer Grewal (SAGE Open Medical Case Reports)
Cutaneous metastases from colorectal cancer are an uncommon but critical finding, typically signaling advanced disease with poor prognosis. This case report describes a 64-year-old woman with a limited past medical history who presented to our outpatient dermatology practice with rapidly spreading erythematous, indurated, and nearly verruciform plaques in the groin, vaginal, and perineal region. Biopsy confirmed metastatic adenocarcinoma of colonic origin, and diagnostic imaging, and colonoscopy revealed stage IV colorectal cancer involving extensive cutaneous, lymphatic, and visceral metastases. Unfortunately, the patient had not received routine colorectal cancer screening, despite a positive family history. Due to extensive disease, palliative radiation was not an option, and systemic chemotherapy was initiated. This case emphasizes the need for awareness of cutaneous metastases as a potential initial presentation of undiagnosed malignancies, the importance of routine colorectal cancer screening, and timely biopsy of suspicious skin lesions for early diagnosis and management.